(untitled) (Experimental biology, 2016)
Laboratory studies have shown that the application of vermicompost in the amount of 20% contributes to the improvement of growth parameters and survival of seedlings Scorzonera tau-saghyz. So, when you make vermicompost average height and number of leaves were almost 1.5 times, the dry weight of the aboveground part of seedlings tau sagyz more than 2 times, the survival rate of seedlings by 7.1% higher than in the controls. Most of the studied morphological parameters of the root system Scorzonera tau-saghyz did not differ significantly, while the number of lateral roots of the main root, and the maximum length of lateral roots adventitious roots 1st order when making vermicompost were, respectively, 2 and 4 times higher than in controls. The use of vermicompost can substantially contribute to the development of cost-effective modern biotechnology aimed at restoring the strength of nature and getting a commercial rubber root Scorzonera tau-saghyz.